2020
DOI: 10.1016/j.adolescence.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relation among disturbed sleep due to social media use, school burnout, and academic performance

Abstract: Introduction: Previous studies have revealed the signiicant inluence of electronic devices, especially social media use, on sleep dificulties among adolescents. In this study, disturbed sleep due to social media use (DSSM) was deined as reduced or troubled sleep caused by nighttimespeciic behaviors such as waking to check updates, being notiied by incoming messages, or postponed bedtime because of social media activities. Inadequate and disturbed sleep during youth interferes with daytime academic eficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 36 publications
(55 reference statements)
2
63
1
2
Order By: Relevance
“…Scholars refer to these negative aspects as the ‘dark side’ of social media and acknowledge that they bring substantial threats to the well-being of consumers ( Dhir et al, 2018 ; Talwar et al, 2019 ). Excessive internet and social media use has been associated with problems such as social media fatigue ( Dhir et al, 2018 , 2019 ), stalking ( Dhir et al, 2021 ; Kaur et al, 2021 ), the fear of missing out ( Przybylski et al, 2013 ), problematic sleep ( Evers et al, 2020 ; Tandon et al, 2020 ; Dhir et al, 2021 ), perceived overloads ( Zhang et al, 2016 ), cyber-slacking ( Nusrat et al, 2021 ), compulsive social media use ( Tandon et al, 2020 ; Dhir et al, 2021 ), and the dissemination of fake news ( Talwar et al, 2019 , 2020a ). The latter is of particular concern for society ( Talwar et al, 2020a ) because not only does it have profound individual, but also political ( Allcott and Gentkow, 2017 ), economic ( Clarke et al, 2020 ), and financial ( Visenti et al, 2019 ) consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars refer to these negative aspects as the ‘dark side’ of social media and acknowledge that they bring substantial threats to the well-being of consumers ( Dhir et al, 2018 ; Talwar et al, 2019 ). Excessive internet and social media use has been associated with problems such as social media fatigue ( Dhir et al, 2018 , 2019 ), stalking ( Dhir et al, 2021 ; Kaur et al, 2021 ), the fear of missing out ( Przybylski et al, 2013 ), problematic sleep ( Evers et al, 2020 ; Tandon et al, 2020 ; Dhir et al, 2021 ), perceived overloads ( Zhang et al, 2016 ), cyber-slacking ( Nusrat et al, 2021 ), compulsive social media use ( Tandon et al, 2020 ; Dhir et al, 2021 ), and the dissemination of fake news ( Talwar et al, 2019 , 2020a ). The latter is of particular concern for society ( Talwar et al, 2020a ) because not only does it have profound individual, but also political ( Allcott and Gentkow, 2017 ), economic ( Clarke et al, 2020 ), and financial ( Visenti et al, 2019 ) consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The association between excessive or problematic SMP use and sleep-related issues is one such individual-level consequence that has gained attention in the past five years. This attention can be attributed to scholars' recognition that the steadily escalating integration of SMPs into human lives has led to the blurring of boundaries between daytime and nocturnal SMP use (Exelmans and Scott, 2019; Tandon et al , 2020; Evers et al , 2020), especially within periods of sleep latency. Researchers posit that such nocturnal SMP use can have detrimental effects on individuals' health and well-being (Xue et al , 2018; Tandon et al , 2020; Whelan et al , 2020; Evers et al , 2020), and consequently, we argue that nocturnal SMP use may be considered to be a part of the dark side of social media.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in the United States ( 26 ) reported that the association between time spent using the computer, playing video games, and watching television reduced the attention in class, according to teachers' report, mediated by daily sleeping hours (β = −0.08; p -value ≤ 0.001). In addition, a study conducted in Taiwan ( 42 ) found that disturbed sleep due to social media had an indirect effect (β = −0.07; p -value ≤ 0.05) on school performance. It is known that the blue light produced by screens alters the production of melatonin and, therefore, the rhythm of sleep, which in turn affects cognition ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%